K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

30 tháng 3 2020

a, 5xy(x+3y)

b, (x-1)(3+5x)

c, (x-y+3)(x-y-3)

30 tháng 3 2020

a)\(5x^2y+15xy^2=5xy\left(x+y\right)\)

b) \(3x-3+5x\left(x-1\right)=3\left(x-1\right)+5x\left(x-1\right)=\left(x-1\right)\left(3-5x\right)\)

c)\(x^2-2xy-9+y^2=\left(x^2-2xy+y^2-9\right)=\left(x-1\right)^2-9=\left(x-1-9\right)\left(x-1+9\right)=\left(x-10\right)\left(x+8\right)\)

4 tháng 9 2021

x2-2xy+y2+3x-3y-10

= (x-y)2+3(x-y)-10

= [(x-y)2+5(x-y)]-[2(x-y)+10]

= (x-y)(x-y+5)-2(x-y+5)

= (x-y+5)(x-y-2)

Ta có: \(x^2-2xy+y^2+3x-3y-10\)

\(=\left(x-y\right)^2+3\left(x-y\right)-10\)

\(=\left(x-y+5\right)\left(x-y-2\right)\)

4 tháng 9 2021

\(\left(x^2+5x-3\right)\left(x^2+5x-5\right)-15=\left(x^2+5x-3\right)\left(x^2+5x-3-2\right)-15=\left(x^2+5x-3\right)^2-2\left(x^2+5x-3\right)+1-16=\left(x^2+5x-3-1\right)^2-4^2=\left(x^2+5x-4\right)^2-4^2=\left(x^2+5x-8\right)\left(x^2+5x\right)=x\left(x+5\right)\left(x^2+5x-8\right)\)

\(\left(x^2+5x-3\right)\left(x^2+5x-5\right)-15\)

\(=\left(x^2+5x\right)^2-8\left(x^2+5x\right)-15\)

\(=x\left(x+5\right)\left(x^2+5x-8\right)\)

26 tháng 6 2018

2   \(x^7+x^5+1=x^7+x^6+x^5-x^6+1=x^5\left(x^2+x+1\right)-\left(x^6-1\right)=x^5\left(x^2+x+1\right)-\left(x^3-1\right)\left(x^3+1\right)\)

\(=x^5\left(x^2+x+1\right)-\left(x-1\right)\left(x^2+x+1\right)\left(x^3+1\right)=\left(x^2+x+1\right)\left(x^5-\left(x-1\right)\left(x^3+1\right)\right)\)

\(=\left(x^2+x+1\right)\left(x^5-x^4+x^3-x+1\right)\)

1   \(x^3-5x^2+3x+9=x^3+x^2-6x^2-6x+9x+9=x^2\left(x+1\right)-6x\left(x+1\right)+9\left(x+1\right)\)

\(=\left(x^2-6x+9\right)\left(x+1\right)=\left(x-3\right)^2\left(x+1\right)\)

1 tháng 8 2019

b) \(a^6-b^3\)

\(=\left(a^2\right)^3-b^3\)

\(=\left(a^2-b\right)\left(a^4+a^2b+b^2\right)\)

c) \(x^4-1\)

\(=\left(x^2\right)^2-1^2\)

\(=\left(x^2-1\right)\left(x^2+1\right)\)

\(=\left(x-1\right)\left(x+1\right)\left(x^2+1\right)\)

28 tháng 12 2017

\(3x^2-5x-8\)

\(=3x^2+3x-8x-8\)

\(=\left(3x^2+3x\right)-\left(8x+8\right)\)

\(=3x\left(x+1\right)-8\left(x+1\right)\)

\(=\left(3x-8\right)\left(x+1\right)\)

28 tháng 12 2017

3x2 - 5x - 8 = 3x2 + 3x - 8x - 8 = ( 3x2 + 3x ) - ( 8x + 8 )

= 3x( x + 1 ) - 8( x + 1 ) = ( 3x - 8 )( x + 1 )

15 tháng 12 2015

Nguyen Huu The lih tih, ko lm thì thôi đi